2021
DOI: 10.1101/2021.09.18.460913
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individualised computational modelling of immune mediated disease onset, flare and clearance in psoriasis

Abstract: Despite increased understanding about psoriasis pathophysiology, currently there is a lack of predictive computational models. We developed a personalisable ordinary differential equations model of human epidermis that features two stable steady states: healthy skin and psoriasis. In line with experimental data, an immune stimulus initiated transition from healthy skin to psoriasis and apoptosis induced by UVB phototherapy returned the epidermis back to the healthy state. The flexibility of our model permi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…A previous computational study [10] showed that the cell population ratio remained the same in both healthy and psoriasis. In addition, the overall number of epidermal cells is known to increase by up to two to five times as compared to the healthy epidermis [25,33].…”
Section: Cell Population Densitymentioning
confidence: 89%
See 4 more Smart Citations
“…A previous computational study [10] showed that the cell population ratio remained the same in both healthy and psoriasis. In addition, the overall number of epidermal cells is known to increase by up to two to five times as compared to the healthy epidermis [25,33].…”
Section: Cell Population Densitymentioning
confidence: 89%
“…The growth model for both healthy and psoriatic epidermis are based on various nutrients and immune cytokines that have been found in literature and in clinical studies [7,10,11]. Cell division of proliferative stem and TA cells are based on having two interconvertible modes as mentioned in [12] where proliferative cells change their division type based on an expanding or balanced state.…”
Section: Cell Growthmentioning
confidence: 99%
See 3 more Smart Citations